A new species of Clematis L. (Ranunculaceae) from Iran - Habibi, Meisam; Nohooji, Majid Ghorbani; Baladehi, Mohammadhadi Heidari; Azizian, Dina (Phytotaxa, 2014)
After extensive sampling and investigations of the genus Clematis from various locations in Iran, Clematis iranica is introduced as a new species. The diagnosis, description and illustration of the new species are presented here. The affinities and differences to the most closely related species (C. orientalis) are presented based on morphological, cytological, palynological and anatomical characters.